A Comparative Analysis Of Hijazi Salafi Opinions In Indonesia And Ibn Taymiyyah’s Perspective On The Democratic Government System: A Siyasah Syar’iyyah Approach - Muhammad Azrul Amirullah (Kodifikasia, 2026)
The relationship between Islam and democracy remains one of the most contested issues in contemporary Islamic political thought. In Indonesia, where democracy serves as the constitutional system of government, the debate is particularly evident among Hijazi Salafi groups, which generally reject democracy on the grounds that it contradicts the principle of divine sovereignty (al-hukmu lillah) and places legislative authority in the hands of human beings rather than Allah. This study aims to analyze the opinions of Hijazi Salafi scholars in Indonesia regarding the democratic government system and compare them with Ibn Taymiyyah’s political thought through the framework of siyāsah shar‘iyyah. Employing normative legal research with a library research approach, the study examines primary sources, including Ibn Taymiyyah’s As-Siyāsah al-Shar‘iyyah and Majmū‘ al-Fatāwā, as well as secondary sources consisting of books, journal articles, and scholarly works on Islamic political thought, democracy, and Salafism. The findings reveal that the Hijazi Salafi rejection of democracy is primarily based on concerns regarding popular sovereignty, secular legislation, and unrestricted freedom. In contrast, Ibn Taymiyyah’s conception of governance emphasizes justice (al-‘adl), public welfare (maṣlaḥah), consultation (shūrā), accountability, and leadership legitimacy derived from public consent. Although Ibn Taymiyyah did not explicitly endorse democracy as a political system, several substantive elements of his political thought correspond with democratic principles, particularly regarding leadership selection, public participation, limitation of political power, and the protection of societal interests. This study argues that Ibn Taymiyyah’s siyāsah shar‘iyyah provides a more flexible and pragmatic framework than the absolute rejection of democracy advanced by contemporary Hijazi Salafi groups. The study contributes to contemporary discussions on Islam and democracy by offering a normative model that integrates Islamic political values with modern governance principles.